Constructing a new developmentally moderated model of English instruction with focus-on-form for Malaysian public preschools. - Mohamed Salleh, Rabiah Tul Adawiyah (2019)
The aim of this paper is to introduce a new framework on English language learning at Malaysian public preschools. At the preschool level in Malaysia, all preschools (public and private ones) are required to follow the guidelines stated in Standard National Preschool Curriculum (SNPC). However, the SNPC is very general and the Ministry also does not supply any textbook, which leads to some preschools to supplement their curriculum by subscribing to various education franchisors available on the market such as Smart Reader, Q-DEES, Kinderland and Montessori. Therefore, this research aims to develop a model of English learning based on developmentally moderated focus-on-form instruction(DMFonF), focusing on public preschools. The study is longitudinal quasi-experimental research using mixed-method approaches to investigate the effectiveness of DMFonF on Malaysian pre-schoolers for one year. Participants include 90 preschool children from public MOE preschools: Group A (45 children) will receive DMFonF in their English lessons while group B (45 children), will receive no intervention. The tests to evaluate the children's English development include the pre-test, test 1 and test 2 and delayed post-test. The outcome of this research will lead to a new framework that will assist teachers, linguists, and syllabus-designers to create a developmentally moderated English curriculum.